The long agony of a radicalism in crisis. Adaptation, breakdown and bowing down of the UCR in the Macrist era - Adriana Gallo (Revista Colección, 2018)
This paper seeks to analyze the critical situation of a centenary -and once-majority- Argentine political party, the Unión Cívica Radical (UCR), after the formation of the alliance Cambiemos, with the PRO and the Civic Coalition parties. This electoral agreement was celebrated in 2015, in order to support the current president Mauricio Macri, who at that time was the most competitive opponent of Kirchnerism. Here we will try to show that the agreement with the PRO implied a principled backing down by the radicals, who ended up consenting to ambitions that were contrary to their charter and incongrous with their political tradition; that left the party in subordination, having been practically abosorbed into the structure of Cambiemos.